ANALISIS KEPUASAN PASIEN DARI ASPEK PROSEDUR PELAYANAN BPJS KESEHATAN TINGKAT LANJUTAN DI POLI PENYAKIT DALAM RUMAH SAKIT ISLAM SURABAYA JEMURSARI - Siti Nurjanah Siska Lianti; Umi Hanik (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2018)
The implementation of health sevices are still found many shortcomings, although service procedures have been providing but in fact service in the hospital to patient BPJS Kesehatan is not appropriate with exiting services procedures. The main aim of the study was to analyze of patient satisfaction about of service procedures BPJS Kesehatan advanced level in poli penyakit dalam hospital islamic surabaya jemursari. The design of this was analytical deskriptif method. The population in this study were 93 patients in Poli Penyakit Dalam Hospital Islamic Surabaya Jemursari. Tehnique of sampling using Accidental Sampling. The data were collected fromquestionnaires, and processed by SPSS program. The results of this study, showed that 76 respondents most (55.3%) explain to satisfaction about of service procedures BPJS Kesehatan advanced level in poli penyakit dalam hospital islamic surabaya jemursari, while explain to not satisfied about of service procedures BPJS Kesehatan. Based on the test resulth obtained statistically there is significant about of service procedures BPJS Kesehatan which are given effect to patientsatisfaction. From the result of this study, it is recommended tha the health workers continue to increase service procedures BPJS Kesehatan and the BPJS workers to simplify about of service procedures has ben set. And recommended for society continue to increase the confidence towards health care workers and immadiate clarification that is no yet clear.